Fabrication of GaN cantilever on GaN substrate by photo-electrochemical etching. (24th February 2021) - Yamada, Takehiro; Ando, Yuto; Watanabe, Hirotaka; Furusawa, Yuta; Tanaka, Atsushi; Deki, Manato; Nitta, Shugo; Honda, Yoshio; Suda, Jun; Amano, Hiroshi
Abstract: Photo-electrochemical (PEC) etching is a promising technique for fabricating GaN microelectromechanical systems devices. In this study, we demonstrate the fabrication of GaN cantilevers by the bandgap-selective PEC etching of an InGaN superlattice sacrificial layer. By using an InGaN superlattice as a sacrifice layer, we found the PEC etching rate became higher than using a normal InGaN layer. As a result, the InGaN superlattice was completely etched and we fabricated GaN-based cantilevers whose resonance characteristics were measured. The Young's modulus of GaN was determined from the resonance characteristics of GaN cantilevers to be the same as the highest value reported previously.